Checklist of the marine and estuarine Brachyura (Crustacea: Decapoda) of northern and northeastern Brazil - Coelho, Petrônio Alves; de Almeida, Alexandre Oliveira; Bezerra, Luis Ernesto Arruda (Zootaxa, 2008)
A total of 272 species of brachyuran crabs are reported from marine and estuarine environments in northern and northeast Brazil. The checklist is derived from the literature published from 1847 to 2008, and includes all species that have been reported at least once from the study area. It is also partially supported by material deposited in the crustacean collection of the Departamento de Oceanografia, Universidade Federal de Pernambuco, city of Recife, Brazil (DOUFPE). The families containing the highest number of species in northern and northeastern Brazil are Majidae (31), Portunidae (22), Epialtidae (20), Panopeidae (20), and Xanthidae (18). The remaining species are distributed in 39 families. The analysis of the distribution of the species in the region, allows for identification of four patterns of longitudinal distribution (western Atlantic, Amphi-Atlantic, Amphi-American, and circumtropical species) and, in the western Atlantic, six patterns of latitudinal distribution (Virginian, Carolinian, Antillean, Central-South American, Boreal, and Endemic). Two non-indigenous species have also been reported. Most of the species represented in northern and northeastern Brazil have Antillean (94 species; 34.5%) and Carolinian (75 species; 27.6%) pattern of distribution.